Tinjauan Yuridis Tentang Peralihan Hak Atas Tanah yang Akan Digunakan Untuk Jalan Tol Trans Sumatera (Studi Pada BPN Lampung Selatan) - Muhammad Alif Rizqi (Wajah Hukum, 2021)
Soil is an important element in life especially for humans. In the transfer of land rights, the government issued regulations, namely: Government Regulation Number 10 of 1961 concerning land registration amended by regulation number 24 of 1997 concerning land registration contained in article 37 paragraph 1 which reads "transfer of rights to land in unit property rights through sale and purchase. , exchanges, grants, income in the company and other acts of transfer of rights, except the transfer of auction rights which are only registered if it is proven that there are deeds that have been made by PPAT ”. There are two forms of transfer of land rights, namely: transfer and diahlikan. and the Presidential Regulation was then revised by the seventh President of Indonesia, Mr. Joko Widodo with the issuance of Presidential Regulation Number 117 of 2015 concerning Amendments to Presidential Regulation Number 100 of 2014 concerning the Acceleration of Toll Road Development in Sumatra which will soon be added to a total of 24 Sumatra toll road developments.  In writing this journal, the author discusses a problem, namely: How is the implementation of the transfer of land rights to be used for road telling?